The Role of Student Trust in Mediating Service Quality and Student Reputation Against E-WOM - Dadang Munandar; Fajar Rezeki Ananda; Syaifuddin Syaifuddin; Yusniar Lubis; Nasib Nasib (Journal of Educational Science and Technology (EST), 2022)
The purpose of this research is to examine the study titled The Role of the Quality of Student Trust in Mediating the Quality of Student Services and the University's Reputation on Electronic Word of Mouth among students. This study's sample was chosen utilizing a multi-stage sampling technique, beginning with the selection of private institutions using purposive sampling and ending with the selection of students using incidental sampling. In this survey, there were 255 students who represented five private universities in percentage. Descriptive statistics and structural equation modeling were employed in the data analysis (SEM). The study's findings revealed that service quality has a positive and significant effect on electronic word of mouth, university reputation has a positive and significant effect on electronic word of mouth, student trust has a positive but not significant effect on electronic word of mouth, student trust can mediate between service quality and electronic word of mouth, and student trust can moderate the influence of university reputation on electronic word of mouth.